The Emerging Climate Crisis: Thoughts of a Quaker Scientist and Possible Ways Forward - Richard Tuckett (Current Advances in Geography, Environment and Earth Sciences Vol. 6, 2022)
The evidence that anthropogenic carbon emissions are contributing to the increasing temperature of the Earth grows stronger by the year. Whilst impossible to prove, it is suggested that the correlation between carbon dioxide, CO2, concentrations and the temperature of the planet is as strong as it ever can be. It follows that immediate actions both by individuals and governments around the world are absolutely essential to protect everyone against the rising temperatures that are almost inevitable. The data for greenhouse gases are brought up to date to the end of 2020, and the effects of the COVID-19 pandemic on carbon emissions are highlighted since the start of that year. It is increasingly believed that methane, CH4, could prove to be as serious a secondary greenhouse gas as CO2. Possible changes in legislation and lifestyle are suggested for the UK. At a global level and in the hope that such subjects are brought into the open, taxation policies based on excess use of carbon, food and its production, and levels of population in the world are discussed. The author is a practicing member of the Quaker (Society of Friends) religion, and throughout he comes to this problem from a moral viewpoint. Specifically, how the six Quaker Testimonies (i.e. ways we should lead our lives) on Truth and Integrity, Social Justice, Equality, Simplicity, Peace and Sustainability lead him in certain personal directions, and what advice he might give to Governments and World organisations (e.g. the United Nations). A concise explanation of the Quaker religion in the UK in the 21st century is written elsewhere by Rowlands; much of it may surprise many readers.